Helmholtz, the conservation of force and the conservation of vis viva. Issue 1 (2nd January 2019) - Caneva, Kenneth L.
ABSTRACT: This paper investigates the relationship between Helmholtz's formulation of the principle of the conservation of force and the two principles well known in rational mechanics as the principle of vis viva and the principle of the conservation of vis viva . An examination of the relevant literature from Leibniz to Duhamel reveals both Helmholtz's indebtedness to that tradition and his creative refashioning of it as he endeavoured to craft an argument that would both prohibit the construction of a perpetuum mobile and the efficacy of a supposed vital force and demonstrate the necessity of an ontology of mass points subject to attractive and repulsive central forces depending solely on distance.